Study on Compatibility of Waterborne Surface Treatment Coatings. Issue 1 (1st February 2022) - Li, Wenbo; Yang, Yingfei; Song, Dongdong; Zhu, Jiran; Xie, Yi
Abstract: the severe corrosion of power grid equipment has always been an important factor affecting the service life of equipment. Rust transfer technology is used to treat the corroded equipment to improve the corrosion resistance of transmission grid cabinet equipment in high temperature and high humidity environment. Taking acid modified acrylic acid as the main component, the composite conversion solution was obtained by adding phosphoric acid and phytic acid. Through the surface morphology, electrochemical test and adhesion test after rust conversion, the universality and corrosion resistance of the rust conversion solution were analyzed; Combined with zinc phosphate primer and zinc rich primer, the effects of rust conversion solution on the adhesion and salt spray corrosion resistance of the two commercial primers were studied. The compound conversion solution has good rust conversion effect on atmospheric corrosion rust layer, salt spray corrosion rust layer and damp heat corrosion rust layer; The corrosion resistance and adhesion of atmospheric corrosion rust layer are obviously improved after being treated with rust conversion solution. The adhesion of zinc phosphate primer and zinc rich primer on rust conversion solution is 2.1 times and 0.8 times higher than that of atmospheric corrosion rust layer without rust conversion, respectively. The compound rust conversion solution has strong universality and can convert atmospheric corrosion, salt spray corrosion and damp heat corrosion rust layers. At the same time, it has good corrosion resistance, which can significantly improve the corrosion potential of the corroded surface and reduce the corrosion current density. In addition, the composite rust conversion solution can significantly improve the adhesion and corrosion resistance of the primer coating.